DETERMINATION OF SOME PESTICIDE RESIDUES IN APPLE JUICE BY HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - Velkoska-Markovska, Lenche; Petanovska-Ilievska, Biljana; Markovski, Aleksandar (University Ss. Cyril and Methodius in Skopje, 2019)
A new, simple and reliable reversed-phase high-performance liquid chromatography (RP-HPLC) method for determination of 2,4-D ((2,4-dichlorophenoxy)acetic acid), atrazine, malathion, fenitrothion and parathion residues in apple juices has been developed and validated. Successful separation and quantitative determination of analytes were performed on Purospher STAR RP-8e (30 x 4 mm, 3 µm) analytical column, with mobile phase consisted of acetonitrile/water (45/55, V/V), flow rate of 1 mL/min, constant column temperature at 25 0C and UV detection at 220 nm and 270 nm. A solid-phase extraction (SPE) was used for concentration and clean-up of analytes. Specificity, selectivity, linearity, precision, accuracy, limit of detection (LOD) and limit of quantification (LOQ) were tested for the method validation according to European Commission guidelines for pesticide residue analytical methods, and all performance characteristics were found within acceptance criteria. Calibration curves were linear within the range less than 50 % of the maximum residue limit (MRL) values and 20 % above for all investigated pesticides (R2 > 0.95). Under the stipulated conditions, values for relative standard deviations (RSD) of retention times and peak areas were 0.12 % - 0.28 % and 0.08 % - 8.50 %, respectively. The obtained values for recoveries ranged from 93.65 % - 118.62 %, with RSD ≤ 5.64 %. This method was successfully applied for determination of investigated pesticide residues in apple juice samples, which were taken from Macedonian markets. The run time of assay obtained from this chromatography condition was about 4 min.
Keywords: RP-HPLC, SPE, method development, validation